THE EFFECT OF DIFFERENTIATED INSTRUCTION ON STUDENTS’ CRITICAL THINKING SKILLS - Indriyani, Kris; Aprima, Desy (Universitas Indraprasta PGRI, 2025)
The effect of differentiated learning on students' critical thinking skills at Tugu Harum elementary school in the subject of Natural and Social Sciences (IPAS) is the aim of this study. This study employs a quantitative approach, with the Quasi-Experimental Design method being used as a type of non-equivalent control group design. A total of 30 fifth-grade students at elementary school Tugu Harum were selected as the sample for this study. Data collection methods included a 15-item essay test, which was evaluated for validity and credibility. The results showed a very high Cronbach’s Alpha value for the categories. Normality, homogeneity, and hypothesis tests were conducted to analyze the data. The findings indicated that there was a significant difference between the posttest results of the experimental group and the control group. This discovery suggests that the implementation of differentiated learning significantly affects the improvement of students' critical thinking skills. By providing treatments that align with students' readiness, interests, and learning styles, differentiated learning can foster a more active, meaningful, and effective learning process. Therefore, this approach can serve as a creative alternative to enhance the quality of learning in elementary schools, with a particular emphasis on developing critical thinking skills relevant to the 21st century.